IMPLEMENTASI TEKNOLOGI DALAM MENGELOLA PERUBAHAN PENDIDIKAN: DAMPAKNYA TERHADAP EFEKTIVITAS SEKOLAH - R. Mochammad Rachmat; Muhammad Sarkhosyi; Rahmatullah Sidik; H. Abdul Hakim; Ahmad Hamdi; Muhamad Subkhan (YAYASAN PERCIKAN INSAN MANDIRI (PRISMA), 2024)
The implementation of technology in educational change management has become one of the main focuses in efforts to enhance school effectiveness. This study aims to explore the impact of technology use on the change process in educational environments and how it affects school operational effectiveness. The study adopts a qualitative approach with case study methods in several schools that have integrated technology into their managerial strategies. The findings indicate that technology facilitates better communication, eases professional training and development, and improves data accessibility and management. However, challenges such as the need for intensive training and resistance to change were also identified. The study concludes that technology can significantly improve school effectiveness in managing change, but its successful implementation heavily depends on appropriate support and well-planned strategies. Recommendations for schools include developing comprehensive training programs and adaptive change management strategies to maximize the potential of technology in education.